Experimental and numerical studies on dynamic mechanical properties of threads under impact loads. (April 2023) - Amir, Ben; Lomnitz, Alon; Kochavi, Eytan; Gruntman, Shimon; Sadot, Oren
Highlights: Threads act as porous material under dynamic loads. Ten-pitch thread can transfer stress waves with negligible distortions. Rise time differences are related to the different lengths of the threaded adapters. Hard threads are more durable under dynamic loading. Rougher threads can transfer dynamic stress pulses with minimal disturbance. Abstract: Threaded links are widely used in many structures designed to sustain extreme dynamic loads. Therefore, investigation of their behavior under such extreme conditions is crucial. A recent review highlighted a significant gap in understanding the mechanical behavior of threads under impact loads [Warren et al. J Constr Steel Res, 2022;194]. Therefore, this study investigates the effect of thread geometries on stress waves propagating through the threads using two parallel approaches: experimental and numerical simulations. Different threads were manufactured from steel alloys with varying lengths of pitch and tooth geometries. Experiments using a split Hopkinson pressure bar (SHPB) system and a numerical simulation using the LS-DYNA code were performed to characterize the propagation of a stress wave when crossing different threads. The investigation revealed that increasing the tooth height of the threads and the number of teeth reduced the distortion of stress waves produced by the thread. It was also shown that a fine thread could reduce the level of the transmitted stress under dynamic loading, similar to the effect observed when using a porous material. With this feature, it will be possible to design thread connections with the ability to mitigate or transmit dynamic impulse loads.